A Prophet or a Messenger: How Bona Fide a Qur’anic Concept? (American Journal of Islam and Society, 2009)
This paper probes specific questions in the Qur’an on various prophetic phenomenon (e.g., the purpose of revelation to prophets/messengers, the question of sending them, and the meaning of book/scripture) in order to ascertain whether or not the popular theories on their essence have valid Qur’anic support. It hypothesizes that the major conclusions on this subject have no solid Qur’anic evidence, that prophets and messengers are one and the same person, and that the Qur’an uses both terms interchangeably. Specific treatments of the questions (heavily dependent on the Qur’an) are preceded by their simple depiction in a diagram. Fresh attempts are made to redefine the terms prophet and messenger. I begin by reviewing the conclusions of al-Mawardi, al-Qadi ‘Iyad, Ibn Taymiyyah, and Abu Bakr al-Jaza’iri, all of whom have, in what came to be extremely popular concepts, distinguished between prophets and messengers. Following suit, the ideas of some leading western scholars on this subject (e.g., A. J. Winsinck, Joseph Horovitz, and Willem A. Bijlefeld) are also reviewed and assessed.